2022
DOI: 10.3389/fnut.2022.907595
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Juice Flavanones Modulate the Expression of Genes Regulating Inflammation, Cell Interactions and Vascular Function in Peripheral Blood Mononuclear Cells of Postmenopausal Women

Abstract: Grapefruit is a rich source of flavanones, phytochemicals suggested excreting vasculoprotective effects. We previously showed that flavanones in grapefruit juice (GFJ) reduced postmenopausal women’s pulse-wave velocity (PWV), a measure of arterial stiffness. However, mechanisms of flavanone action in humans are largely unknown. This study aimed to decipher molecular mechanisms of flavanones by multi-omics analysis in PBMCs of volunteers consuming GFJ and flavanone-free control drink for 6 months. Modulated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…5 and 9). Previous studies have reported that flavanones naringenin-4′ O -glucuronide (−7.5 kcal mol −1 ) and naringenin-7- O -glucuronide (−7.9 kcal mol −1 ) present potential probability of binding to STAT3, 19 comparable to the result that we found in our study for H7G (−8.66 kcal mol −1 ) and PA (−6.81 kcal mol −1 ). Furthermore, it has been suggested that haringenin-4′ O -glucuronide presents a potential probability of interacting with the ERK1-MAPK signaling protein (−7.6 kcal mol −1 ), 19 also similar to that we found in our study on H7G (−8.55 kcal mol −1 ) and PA (−6.60 kcal mol −1 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…5 and 9). Previous studies have reported that flavanones naringenin-4′ O -glucuronide (−7.5 kcal mol −1 ) and naringenin-7- O -glucuronide (−7.9 kcal mol −1 ) present potential probability of binding to STAT3, 19 comparable to the result that we found in our study for H7G (−8.66 kcal mol −1 ) and PA (−6.81 kcal mol −1 ). Furthermore, it has been suggested that haringenin-4′ O -glucuronide presents a potential probability of interacting with the ERK1-MAPK signaling protein (−7.6 kcal mol −1 ), 19 also similar to that we found in our study on H7G (−8.55 kcal mol −1 ) and PA (−6.60 kcal mol −1 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that flavanones naringenin-4′ O -glucuronide (−7.5 kcal mol −1 ) and naringenin-7- O -glucuronide (−7.9 kcal mol −1 ) present potential probability of binding to STAT3, 19 comparable to the result that we found in our study for H7G (−8.66 kcal mol −1 ) and PA (−6.81 kcal mol −1 ). Furthermore, it has been suggested that haringenin-4′ O -glucuronide presents a potential probability of interacting with the ERK1-MAPK signaling protein (−7.6 kcal mol −1 ), 19 also similar to that we found in our study on H7G (−8.55 kcal mol −1 ) and PA (−6.60 kcal mol −1 ). These in silico results suggest that H7G and PA may interact with these transcription factors and cell signaling proteins, but do not allow us conclude whether these result in the activation or inhibition of the proteins identified as differentially expressed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, here we have only included the studies that demonstrated positive effects of flavonoids on vascular function and analyzed their genomic effects using microarray methods [26][27][28]. In addition, two recent studies of relevance for our analyses [29,30] were also included. In all of these studies, the analyses of global gene expression were conducted in samples of peripheral blood.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previously reported strategy for the systematic literature search [25], we identified five human intervention studies with flavonoids that analyzed global gene expression in peripheral blood cells and demonstrated at least one positive effect on vascular function. General information about each of these studies, referred to as Paper 1 to Paper 5 (Paper 1 [26]; Paper 2 [27]; Paper 3 [28]; Paper 4 [30]; Paper 5 [29]) is presented in Table 1. In these studies, flavonoids of different subclasses were studied: Hesperidin displays relevant role in the nutrigenomic effect of orange juice on blood leukocytes in human volunteers: a randomized controlled cross-over study [26] Healthy, middleaged, moderately overweight men…”
Section: General Overview Of Selected Studies and Degsmentioning
confidence: 99%